IN-VITRO STUDIES ON TURMERIC (CURCUMA) - DR.(MRS.) ADITI PANDEY (International Journal of Pharma and Bio Sciences, 2015)
Turmeric is the common name used for dried rhizome of Curcuma longa L., a monocotyledonous plant belonging to the family Zingiberaceae. Curcumin is responsible for the biological actions of turmeric and comprises of curcumin, demethoxy curcumin and bis demethoxy curcumin. Generally, the commercially produced curcumin is a mixture of the above with curcumin as the main constituent. Turmeric powder, curcumin and its derivatives and many other extracts from the rhizome were found to be bioactive. Tissue culture, an important area of biotechnology can be used to improve the productivity of planting material through enhanced availability of identified planting stock with desired traits.